Perancangan Sistem Informasi Penggajian Pada Cv Juata Jaya Teknik Bekasi - Hamdun Sulaiman; Sinta Rukiastiandari; Mira Retaniama (LPPM Universitas Bina Sarana Informatika, 2022)
Along with the development of the times, human needs for technology are increasing along with the development of information technology that is increasingly rapid. The desire of humans to do things easily and quickly. To improve company performance, it can use information technology, especially computers, companies can manage information quickly and can be superior to other competitors. CV Juata Jaya Teknik is one of the companies engaged in contracting, this company offers contractor services with services that are fast, effective, and flexible, always trying to understand and serve wholeheartedly by realizing customer expectations for security, facilities, effectiveness and efficiency. Changes from time to time make developments in the field of technology increasingly diverse. Starting from the transportation sector, daily needs to the systems that exist in the company. One of them is the employee payroll system, in payroll some calculations are needed that refer to the SOP of the company. So that the system built can be adjusted to the needs and SOP of the company itself. With the employee payroll system application, it can simplify the data processing process quickly, accurately and efficiently so that it can avoid data delays and disharmony